2011
DOI: 10.1124/dmd.111.041152
|View full text |Cite
|
Sign up to set email alerts
|

Increased Systemic Exposure to Rhizoma Coptidis Alkaloids in Lipopolysaccharide-Pretreated Rats Attributable to Enhanced Intestinal Absorption

Abstract: ABSTRACT:Rhizoma coptidis is a rhizome commonly used in traditional Chinese medicine. After oral administration of rhizoma coptidis extract, the plasma concentrations of its effective alkaloid constituents are so low that their systemic therapeutic actions cannot be explained. This study aimed to investigate the influence of lipopolysaccharide (LPS) on the pharmacokinetics of the rhizoma coptidis alkaloids. Pharmacokinetic experiments were performed with rats; both in vitro absorption and efflux experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…Based on the assumption that only the constituents absorbed in the blood have the chance to exhibit the pharmacological effects, we believe that some biotransformed products might play an important role in the efficacy of traditional Chinese medicines. In addition, previous pharmacokinetic investigations proved that after oral administration of Rhizoma coptidis extract, the plasma concentrations of its prototype alkaloids were so low that their systemic therapeutic actions cannot be explained . The contradiction between the definite biological activities and the poor permeability and absorption of alkaloids promoted the hypothesis that the metabolites of the alkaloids may also exert biological activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the assumption that only the constituents absorbed in the blood have the chance to exhibit the pharmacological effects, we believe that some biotransformed products might play an important role in the efficacy of traditional Chinese medicines. In addition, previous pharmacokinetic investigations proved that after oral administration of Rhizoma coptidis extract, the plasma concentrations of its prototype alkaloids were so low that their systemic therapeutic actions cannot be explained . The contradiction between the definite biological activities and the poor permeability and absorption of alkaloids promoted the hypothesis that the metabolites of the alkaloids may also exert biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, the in vivo processes of Chinese herbs are difficult to clarify due to their varied compositions and complex metabolic pathways. Based on the assumption that only the constituents absorbed into the blood have the opportunity to exhibit pharmacological effects, detailed pharmacokinetic studies of the alkaloids, including berberine, coptisine and palmatine, after oral administration of Rhizoma coptidis extract in rat plasma, rabbit plasma and the pharmacokinetic behavior of berberine in the plasma of healthy male volunteers were conducted. However, to the best of our knowledge, few efforts have been made to investigate the metabolic profile of the whole extract of Rhizoma coptidis in human plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, immunofluorescence, immunohistochemical and western blotting analysis indicated that CK inhibited colon tissues’ NF-κB pathway activation in a concentration-dependent manner. As in the inflammation function cycle, the macrophages stimulated and secreted cytokines and then regulated the innate inflammatory systems [18], [19]. According to what we have found, and to verify the functional mechanisms of CK in the intestinal disorder, LPS-stimulated macrophages (RAW 264.7 cells) treated with or without CK or BBR for 10 h, and then cytokines production and signaling pathways were determined in vitro .…”
Section: Introductionmentioning
confidence: 91%
“…For intravenous administration, rats received a 10-mg/kg dose by tail vein injection. Rats were lightly anesthetized using diethyl ether, and blood (approximately 300 µL) was collected from the inner canthus vein at 0.083, 0.25, 0.5, 1, 2, 3, 3.5, 4,6,8,12, and 24 h after the dose. Plasma was obtained by centrifugation at 8000×g for 10 min at 4°C and was stored at −80°C after separation until assayed as described below.…”
Section: Methodsmentioning
confidence: 99%
“…7) Ma et al subsequently found that lipopolysaccharide pretreatment increased systemic exposure to the alkaloids through enhancement of their absorption, which was related to decreased intestinal efflux and metabolism. 8) The distribution of drugs to the brain is determined by various factors including transport across the blood-brain barrier (BBB) and their binding in blood and brain. The BBB plays a vital role in controlling the exchange of endogenous and exogenous substances between the blood and the relevant site.…”
mentioning
confidence: 99%